Prostate-specific antigen kinetics and biochemical control following stereotactic body radiation therapy, high dose rate brachytherapy, and low dose rate brachytherapy: A multi-institutional analysis of 3502 patients. (October 2020) - Levin-Epstein, Rebecca; Cook, Ryan R.; Wong, J. Karen; Stock, Richard G.; Jeffrey Demanes, D.; Collins, Sean P.; Aghdam, Nima; Suy, Simeng; Mantz, Constantine; Katz, Alan J.; Nickols, Nicholas G.; Miszczyk, Leszek; et al.
Highlights: The kinetics of PSA decline differed between SBRT, HDR-BT, and LDR-BT. Lower nPSA, longer decay to nPSA, and greater achievement of PSA <0.2 ng/mL was seen after LDR-BT. Though PSA kinetics and degrees of prostatic ablation differed, biochemical control was similar. Continued PSA decline >4 years post-treatment was predictive of durable biochemical control. Abstract: Background and purpose: Stereotactic body radiation therapy (SBRT), low dose rate brachytherapy (LDR-BT) and high dose rate brachytherapy (HDR-BT) are ablative-intent radiotherapy options for prostate cancer (PCa). These vary considerably in dose delivery, which may impact post-treatment prostate-specific antigen (PSA) patterns and biochemical control. We compared PSA kinetics between SBRT, HDR-BT, and LDR-BT, and assessed their relationships to biochemical recurrence-free survival (BCRFS). Methods and materials: Retrospective PSA data were analyzed for 3502 men with low-risk ( n = 2223; 63.5%), favorable intermediate-risk ( n = 869; 24.8%), and unfavorable intermediate-risk ( n = 410; 11.7%) PCa treated with SBRT ( n = 1716; 49.0%), HDR-BT ( n = 512; 14.6%), or LDR-BT ( n = 1274; 36.4%) without upfront androgen deprivation therapy at 10 institutions from 1990 to 2017. We compared nadir PSA (nPSA), time to nPSA, achievement of nPSA <0.2 ng/mL and <0.5 ng/mL, rates of nPSA <0.4 ng/mL at 4 years, and BCRFS. Results: Median follow-up was 72 months. Median nPSA and nPSA <0.2 ng/mL were stratified by risk group (interaction p ≤ 0.001). Median nPSA and time to nPSA were 0.2 ng/mL at 44 months after SBRT, 0.1–0.2 ng/mL at 37 months after HDR-BT, and 0.01–0.2 ng/mL at 51 months after LDR-BT (mean log nPSA p ≤ 0.009 for LDR-BT vs. SBRT or HDR-BT for low/favorable intermediate-risk). There were no differences in nPSA <0.4 ng/mL at 4 years ( p ≥ 0.51). BCRFS was similar for all three modalities ( p ≥ 0.27). Continued PSA decay beyond 4 years was predictive of durable biochemical control. Conclusion: LDR-BT led to lower nPSAs with longer continued decay compared to SBRT and HDR-BT, but no differences in BCRFS.